1996
DOI: 10.1159/000227620
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Thrombin-Antithrombin Complexes, Latent Coagulation Disorders and Metastatic Spread in Lung Cancer: A Longitudinal Study

Abstract: In patients affected with different tumours, disorders concerning clotting are frequently observed. The biological processes leading to coagulation are probably involved in the mechanisms of metastasis. We studied plasma levels of thrombin-antithrombin III complexes (TAT) in 90 patients affected with lung tumours subgrouped in small cell and non-small cell (NSC) lung cancer: 17 patients had no evidence of disease after surgery (NE); the remaining 73 patients were divided according to the absence (LOC) or the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…The presence of advanced cancer triggered the haemostatic system to a much greater extent than expected after that kind of surgery, and the coagulation activation was further augmented 3 months after the palliative operation. In accordance with the present data, a study on non-small-cell lung cancer has demonstrated decreasing TAT values in patients responsive to therapy and increasing values in those with disease progression (29).…”
Section: Discussionsupporting
confidence: 92%
“…The presence of advanced cancer triggered the haemostatic system to a much greater extent than expected after that kind of surgery, and the coagulation activation was further augmented 3 months after the palliative operation. In accordance with the present data, a study on non-small-cell lung cancer has demonstrated decreasing TAT values in patients responsive to therapy and increasing values in those with disease progression (29).…”
Section: Discussionsupporting
confidence: 92%
“…Differential levels of serum ATR in patients with EACa, SCCa and ACCa have not been previously reported although the increased levels of ATRthrombin complex have been demonstrated in the plasma of lung cancer patients [26] as well as patients with the various gynecological cancers [27]. Among the latter, the highest levels of ATR-thrombin complex were detected in patients with ovarian carcinoma, followed by cervical cancer patients and endometrial cancer patients, respectively [27].…”
Section: Discussionmentioning
confidence: 88%
“…A prolonged prothrombin time, 304 as well as increased levels of individual clotting factors including factors V, VIII, IX, and XI are often observed. Other useful markers that are indicative for ongoing activation of the coagulation cascade in cancer patients in vivo include protease-inhibitor complexes such as thrombin-antithrombin III (TAT) complexes 307 and circulating endothelium activation products such as thrombomodulin (TM). 308 Plasma levels of uPA were increased in some patients with endometrial and cervical cancer, 309,310 in pancreatic and colorectal carcinomas, 311 cancer of the prostate 312 and liver.…”
Section: The Hypercoagulable Statementioning
confidence: 99%